The potential of Sclerodermus brevicornis as a native biocontrol agent of invasive wood-boring beetles in European agro-forest ecosystems - Mohamed, Mohamed Khadar Abdi (2020)
This thesis presents a series of experiments aimed to develop the potential of the parasitoid wasp Sclerodermus brevicornis (Hymenoptera: Bethylidae) as an agent of biological control of invasive wood boring beetles. This development includes relatively straightforward considerations, such as finding suitable alternative hosts for its efficient mass rearing and, because Sclerodermus are quasi-social, it also includes gaining an understanding of the reproductive behaviours that make up its unusual life-history, with particular focus on the importance of interactions between kin. The first chapter introduces the economic impact of invasive wood-boring long-horned beetles on forests and biological pest control, especially using parasitoids, including bethylids. Next, the underlying principles of the experiments performed are presented. The first experimental work (Chapter 2) deals with the efficiency of rearing S. brevicornis on a new factitious (alternative) host. The suitability of rice moth (Corcyra cephalonica) larvae is explored and it is concluded that this species is suitable to mass-rear S. brevicornis efficiently, even though it is a lepidopteran and the natural hosts of Sclerodermus are coleopterans. The second set of experiments (Chapters 3 and 4) explores effects of kinship between Sclerodermus co-foundresses. The potentially interacting roles of host size, foundress number and relatedness as evolutionary influences on cooperative reproduction were evaluated. Kinship effects were found consistently, notably in the timing of host attack. Individual females appear to be reluctant to attack large and dangerous hosts unless the benefits of their success will be shared among their kin. It is concluded that while cooperative reproduction in Sclerodermus can be selected for by direct fitness benefits, it will be subject to modification by inclusive fitness considerations. On the basis that quasi-sociality probably evolved from a less complex social system, and with the aspiration of generating insights into transitions between ‘levels’ of sociality, the third set of experiments (Chapters 5 and 6) explored host size, foundress number and kinship effects in two members of the bethylid genus Goniozus: these are naturally sub-social, exhibiting maternal care but not cooperative reproduction. Effects of kinship were found in both species, most notably on the sex ratio of offspring broods. In G. nephantidis sex ratios of multi-foundress groups responded to foundress number when females were non-siblings but not when they were siblings. In G. legneri, sex ratios were less female biased when mothers had mated with a male from a different strain. Both these effects are in the direction predicted by sex ratio theory that considers variation in relatedness within local mating population structures. Although the focus of these studies is on understanding the reproductive biology of Sclerodermus, along with Goniozus, to explore the origins and maintenance of quasi-sociality, advances in this area have potential to enhance the deployment of these parasitoids in biological pest control. They can feed into the design of mass-rearing and release programmes for Sclerodermus brevicornis, and thus contribute to tackling wood-boring long-horned beetles that are invasive in European agroforestry.